Z-boson production in p-Pb collisions at √sNN=8.16 TeV and Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Berdnikova, Anastasia; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Leardini, Lucia; Martin, Nicole Alice; et al. (Journal of high energy physics, 2020)
Measurement of Z-boson production in p-Pb collisions at sNN$$ \sqrt{s_{NN}} $$= 8.16 TeV and Pb-Pb collisions at sNN$$ \sqrt{s_{NN}} $$= 5.02 TeV is reported. It is performed in the dimuon decay channel, through the detection of muons with pseudorapidity −4 < ημ < −2.5 and transverse momentum pTμ$$ {p}_{T}^{μ } $$> 20 GeV/c in the laboratory frame. The invariant yield and nuclear modification factor are measured for opposite-sign dimuons with invariant mass 60 < mμμ < 120 GeV/c2 and rapidity 2.5 < ycmsμμ$$ {y}_{cms}^{μ μ} $$< 4. They are presented as a function of rapidity and, for the Pb-Pb collisions, of centrality as well. The results are compared with theoretical calculations, both with and without nuclear modifications to the Parton Distribution Functions (PDFs). In p-Pb collisions the center-of-mass frame is boosted with respect to the laboratory frame, and the measurements cover the backward (−4.46 < ycmsμμ$$ {y}_{cms}^{μ μ} $$< −2.96) and forward (2.03 < ycmsμμ$$ {y}_{cms}^{μ μ} $$< 3.53) rapidity regions. For the p-Pb collisions, the results are consistent within experimental and theoretical uncertainties with calculations that include both free-nucleon and nuclear-modified PDFs. For the Pb-Pb collisions, a 3.4σ deviation is seen in the integrated yield between the data and calculations based on the free-nucleon PDFs, while good agreement is found once nuclear modifications are considered.
The ALICE Collaboration, S. Acharya, V. Anguelov, A. Berdnikova, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, M.K. Köhler, L. Leardini, N.A. Martin, J.A. Lopez, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M. Schmidt, J. Stachel, S. Stiefelmaier, B. Windelband, A. Yüncü [und viele weitere]
Im Titel steht sNN unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 29.10.2020